Minimally invasive partial versus total adrenalectomy for unilateral primary hyperaldosteronism: a retrospective, multicenter matched-pair analysis using the new international consensus on outcome measures - Billmann, Franck; Billeter, Adrian; Thomusch, Oliver; Keck, Tobias; El Shishtawi, Sherehan; Langan, Ewan A.; Strobel, Oliver; Müller, Beat P. (Surgery, 2021)
Background - Primary hyperaldosteronism is a recognized risk factor for myocardial infarction, stroke, and atrial fibrillation. Minimally invasive adrenalectomy is the first-line treatment for localized primary hyperaldosteronism. Whether minimally invasive adrenalectomy should be performed using a cortex-sparing technique (partial minimally invasive adrenalectomy) or not (total minimally invasive adrenalectomy) remains a subject of debate. The aim of our study was to evaluate the clinical and biochemical efficacy of both procedures and to examine the morbidity associated with partial minimally invasive adrenalectomy versus total minimally invasive adrenalectomy in a multicenter study. - Methods - Using a retrospective study design, we determined the efficacy, morbidity, and mortality of partial minimally invasive adrenalectomy and total minimally invasive adrenalectomy. The Primary Aldosteronism Surgical Outcome Study classification was used to explore clinical and biochemical success. Matched-pair analysis was used in order to address possible bias. - Results - We evaluated 234 matched patients with unilateral primary hyperaldosteronism: 78 (33.3%) underwent partial minimally invasive adrenalectomy, and 156 (66.7%) were treated with total minimally invasive adrenalectomy. Complete clinical success was achieved in 40.6%, and partial clinical success in an additional 52.6% of patients in the entire cohort. Complete biochemical success was seen in 94.0% of patients. Success rates and the incidence of perioperative complications were comparable between groups. Both postoperative hypocortisolism (11.5% vs 25.0% after partial minimally invasive adrenalectomy and total minimally invasive adrenalectomy, respectively; P < .001) and postoperative hypoglycemia (2.6% vs 7.1% after partial minimally invasive adrenalectomy and total minimally invasive adrenalectomy; P = .039) occurred more frequently after total minimally invasive adrenalectomy. - Conclusion - Our study provides evidence that patients with unilateral primary hyperaldosteronism are good surgical candidates for partial minimally invasive adrenalectomy. Not only is the surgical outcome comparable to that of total minimally invasive adrenalectomy, but also postsurgical morbidity, particularly in terms of hypocortisolism and hypoglycemia, may be reduced.
Gesehen am 05.08.2021
First published: 17 October 2020